Antibacterial and fungicidal activities of ethanol extracts from Cotinus coggygria, Rhus typhina, R. trilobata, Toxicodendron orientale, Hedera helix, Aralia elata, Leptopus chinensis and Mahonia aquifolium - V. V. Zazharskyi; P. О. Davydenko; O. М. Kulishenko; I. V. Borovik; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2020)
The search for promising plants with bactericidal and fungicidal activity is of great interest for practical and veterinary medicine, This article reveals the high antibacterial effect of the use of ethanol extracts from 8 species of plants of the families Anacardiaceae (Cotinus coggygria Scop., Rhus typhina L., Rhus trilobata Nutt. and Toxicodendron orientale Greene), Araliaceae (Hedera helix Linnaeus and Aralia elata (Miq.) Seem.), Phyllanthaceae (Leptopus chinensis (Bunge) Pojark.), Berberidaceae (Mahonia aquifolium (Pursh) Nutt.) against 23 strains of bacteria and one strain of fungi. The in vitro experiment revealed the zone of inhibition of growth of colonies exceeding 8 mm during the application of ethanol extracts of C. coggygria against twelve species of microorganisms (Enterococcus faecalis, Escherichia coli, Staphylococcus aureus, S. epidermidis, Bacillus cereus, Listeria ivanovi, Corynebacterium xerosis, Rhodococcus equi, Proteus vulgaris, P. mirabilis, Serratia marcescens and Candida albicans), Rhus typhina – against twelve species (E. faecalis, E. coli, S. aureus, S. epidermidis, L. ivanovi, C. xerosis, Rh. equi, P. vulgaris, Salmonella typhimurium, S. adobraco, S. marcescens and C. albicans), Rhus trilobata – against fourteen (E. faecalis, E. сoli, S. аureus, S. epidermidis, B. subtilis, B. cereus, L. ivanovi, C. xerosis, Rh. equi, P. vulgaris, P. mirabilis, Рseudomonas аeruginosa, Yersinia enterocolitica and C. albicans), Toxicodendron orientale – against eleven (E. faecalis, S. аureus, L. іnnocua, C. xerosis, Campylobacter jejuni, Rh. equi, P. vulgaris, P. mirabilis, Р. аeruginosa and C. albicans), Hedera helix – against seven (S. аureus, S. epidermidis, L. monocytogenes, C. jejuni, Rh. equi, P. vulgaris and C. albicans), Aralia elata – against nine (E. coli, S. aureus, B. cereus, C. xerosis, P. vulgaris, P. mirabilis, S. typhimurium, S. marcescens and C. albicans), Leptopus chinensis – only against four (E. coli, S. epidermidis, B. cereus and P. mirabilis) and Mahonia aquifolium – against only three species (S. epidermidis, C. jejuni and P. vulgaris). As a result of the research, the most promising for studying in future regarding in vivo antibacterial activity were determined to be C. coggygria, Rhus typhina, R. trilobata, Toxicodendron orientale and Aralia elata.